Changes in Cytokines Concentration Following Long-Distance Running: A Systematic Review and Meta-Analysis - Alves, Micael Deivison de Jesus; Silva, Devisson dos Santos; Pereira, Erika Vitoria Moura; Pereira, Danielle Dutra; de Sousa Fernandes, Matheus Santos; Santos, Dayane Franciely Conceição; Oliveira, Davi Pereira Monte; Vieira-Souza, Lucio Marques; Aidar, Felipe J.; de Souza, Raphael Fabricio (Frontiers in Physiology, 2022)
Long-distance running is an exhausting effort for the whole organism. Prolonged aerobic exercise induces changes in inflammatory markers. However, predicting muscle damage in response has limitations in terms of selecting biomarkers used to measure inflammatory status. The present study conducts a systematic review and meta-analysis of articles focusing in ultra-marathon, marathon, and half-marathon and levels of cytokines. The search was conducted in PubMed, Web of Science, and Scopus databases, resulting in the inclusion of 76 articles. IL-6 was highlighted, evaluated in 62 studies and show increase in the standard mean difference (SMD): half-marathon (SMD -1.36; IC 95%: -1.82, -0.89, Ch2:0.58; tau2:0.00; p<0.0001), marathon (SMD -6.81; IC 95%: -9.26, -4.37; Ch2:481.37 tau2:11.88; p<0.0001) and ultra-marathon (SMD -8.00 IC 95%: -10.47, -5.53; Ch2:328.40; tau2:14.19; p<0.0001). In contrast meta-regression analysis did not show relationship to the running distance (p= 0.864). The meta-analysis evidenced increase in the concentration of IL-1ra (p<0.0001), IL-1b (p<0.0001), IL-8 (p<0.0001), IL-10 (p<0.0001) and TNF-a (p<0.0001). Reduction in IL-2 (p<0.0001) and INF-y (p<0.03) and no change in the IL-4 (p<0.56). The number of studies evaluating the effect of adipokines was limited, however Leptin and Resistin were recurrent. The effects of an acute bout of prolonged aerobic exercise will protect against chronic systemic inflammation. The time to return to baseline values showed a substantial and dose-dependent relationship with run volume. The concentration of IL-6 was robustly studied and the marathon running was the most explored. Network of endocrine interactions in which circulating factors, released in extreme exercises, interplay through inter-organ crosstalk and physiologic changes were expressed. The running volume variability was able to modulate compounds that play a fundamental role in the maintenance of homeostasis and cell signaling.